4
$\begingroup$

If $\displaystyle S = \sum_{n=1}^{\infty}\frac{\sin (n)}{n}.$ Then value of $2S+1 = $

Using Fourier Series Transformation I am Getting $2S+1=\pi$

But I want to solve it Using Euler Method and Then Use Logarithmic Series.

$\bf{My\; Try::}$ Using $\displaystyle \sin (n) = \left(\frac{e^{in}-e^{-in}}{2i}\right)$. So $\displaystyle S = \sum_{n=1}^{n}\frac{\sin (n)}{n} = \frac{1}{2i}\sum_{n=1}^{\infty}\frac{e^{in}}{n}-\frac{1}{2i}\sum_{n=1}^{\infty}\frac{e^{-in}}{n}$

Now Using $\displaystyle \ln(1-x) = -x-\frac{x^2}{2}-\frac{x^3}{3}...............\infty$

So Let $\displaystyle S = -\frac{1}{2i}\ln(1-e^{i})+\frac{1}{2i}\ln(1-e^{-i})$

Now How can I solve after that

Help me

Thanks

$\endgroup$
  • 1
    $\begingroup$ I am fairly sure that your series converges only conditionally, in which case the rearrangements you are doing are not justified. $\endgroup$ – Ian Jul 27 '14 at 16:41
5
$\begingroup$

Rewrite what you have as:

\begin{align} 2S =& i \ln(1-e^i) -i \ln(1 - e^{-i} ) \\ =& i \ln \left (\frac{1-e^i}{1-e^{-i}} \right ) \\ =&i \ln \left ( -e^{i} \frac{1- e^{-i}}{1-e^{-i}} \right ) \\ =& i \big ( \ln ( -e^{i}) \big) \\ =& i \big ( \ln ( e^{-i \pi} e ^{i} \big ) \\ =& i \big ( \ln ( e^{ i(1 -\pi)} \big ) \\ =& i \big( i ( 1- \pi) \big)\\ =& \pi -1 \\ \end{align}

by choosing the right branch.

$\endgroup$
  • $\begingroup$ To jeb, Thanks for your s Nice solution, would You like to explain me How can you get $\ln(-e^{i}) = i(1-\pi)$, Thanks $\endgroup$ – juantheron Jul 28 '14 at 0:08
  • $\begingroup$ I'll add one step that should clarify it. Namely , $-1 = \exp( (2n+1)\pi i)$. We have to choose the proper branch though, which is how we can obtain the correct answer and shows the "iffyness" of the series splitting you did. $\endgroup$ – Jeb Jul 28 '14 at 16:40
0
$\begingroup$

my attempt :

$$\ \ S=\sum_{n=1}^{\infty } \frac{sin(n)}{n}=\sum_{n=1}^{\infty } = \int_{0}^{\infty } e^{-nw}\sin(n)dw\\ \\ \\$$

$$\therefore S=Im\int_{0}^{\infty }\sum_{n=1}^{\infty }e^{-(w-i)n}dw=Im\ \int_{0}^{\infty }\frac{1}{e^{w-i}}dw=Im\int_{0}^{\infty }\frac{dw}{cos(1)e^{w}-isin(1)e^{w}-1}\\ \\ \\$$

$$\therefore S=Im\int_{0}^{\infty }\frac{e^{w}cos(1)-1+isin(1)e^{w}}{(cos(1)e^{w}-1)^{2}+(sin(1)e^{w})^{2}}dw=\int_{0}^{\infty }\frac{sin(1)\ e^{-w}}{sin^{2}(1)+(cos(1)-e^{-w})^{2}}dw\\ \\ \\$$

$$\therefore S=\lim_{w\rightarrow \infty }\ tan^{-1}\left ( \frac{cos(1)-e^{-w}}{sin(1)} \right )-tan^{-1}\left ( \frac{cos(1)-1}{sin(1)} \right )\\ \\ \\$$

$$\therefore S=tan^{-1}\left ( cot(1) \right )-tan^{-1}\left ( cot(1)-csc(1) \right )=\frac{\pi }{2}-1+\frac{1}{2}=\frac{1}{2}\left ( \pi -1 \right )$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.